Leaving the Faith, Preserving the Self: Identity Processes among Former Sweden-Finnish Conservative Laestadian Siblings - Niskanen, Anoo (Approaching religion, 2026)
This article examines how identity motives shape siblings’ disaffiliation from the Conservative Laestadian revival movement in a Sweden-Finnish context, highlighting apostasy as a multifaceted identity process marked by renegotiation between inherited and emerging identities. Drawing on life-story interviews, the study shows that religious exit is influenced by age, motivational structures and family relations: adolescent departures were accompanied by destructive behaviour, while adult apostasy involved reflection and negotiation within the family. Although the siblings left Conservative Laestadianism, some retained elements of Christian faith, suggesting reformulation rather than outright rejection. By situating these narratives within Identity Process Theory and Motivated Identity Construction Theory, the article demonstrates how motives such as continuity, belonging and psychological coherence shape religious identity processes. The findings also reveal the risks of marginalization and the vacuum state described in role-exit theory, where individuals feel suspended between identities and struggle to establish new roles. By foregrounding sibling dynamics and motivational structures, this article contributes new insights into how religious disaffiliation unfolds as an ongoing negotiation of continuity and belonging.